2002
DOI: 10.19173/irrodl.v2i2.52
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Online Learning to Campus: The hybridization of teaching and learning at Brigham Young University

Abstract: The primary purpose of Brigham Young University (BYU) is to provide students with a combination of sacred and secular education often described as the “BYU experience.” Achieving this purpose is challenged by the rapid growth in Church membership and an enrollment cap of 30,000 students. To address these challenges, BYU sponsors the use of technology to bridge the gap between the increased Church membership and the number of students allowed under the enrollment caps. This institutional case study shows how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 11 publications
(2 reference statements)
1
9
0
1
Order By: Relevance
“…Discussion board on Blackboard could also be used to create opportunities for interactions between learners-learners and instructor-learners. The activities created should also supplement and not overload the students as it has been reported that E-learning often suffers from making large amounts of information available for students to absorb independently [15].…”
Section: University's Blended Learning Initiativesmentioning
confidence: 99%
“…Discussion board on Blackboard could also be used to create opportunities for interactions between learners-learners and instructor-learners. The activities created should also supplement and not overload the students as it has been reported that E-learning often suffers from making large amounts of information available for students to absorb independently [15].…”
Section: University's Blended Learning Initiativesmentioning
confidence: 99%
“…Learner authority means the combination of freedom, power and legitimacy (Goodman, 2010). Critics of traditional e-learning systems emphasise that they completely lack student authority (Waddoups & Howell, 2002). In terms of BL, learners might choose when, how and why completing tasks.…”
Section: Learner Authoritymentioning
confidence: 99%
“…-increase in the level of active learning strategies used (Collis, 2003;Morgan, 2002); the learner rather than the teacher becomes the center of the learning process (Hartman, Dziuban, &Moskal, 1999;Morgan, 2002); -peer-to-peer learning gets greater emphasis (Collis, 2003); -flexibility in meeting individual differences and learning styles increased mentoring of individual learners (Voci& Young, 2001;Waddoups& Howell, 2002); -the possibility of social interaction and easy communication with distant experts, mentors, professionals, or peers (Levine & Wake, 2000); -increased access and convenience to instructional materials (Collis, 2003;Morgan, 2002;Singh & Reed, 2000); -reducing learning costs compared to other learning systems (Bersin& Associates, 2003;Singh & Reed, 2001); -using instructional technology tools and applications in the process of design, implementation and utilization of instructional materials (Driscoll, 2002;Dziuban, Hartman, &Moskal, 2004;Rossett, 2002;Thomson, 2002); and -disseminating of knowledge through internet which eliminates information technology literacy (Graham, 2004;Driscoll, 2002).…”
Section: Why Blending?mentioning
confidence: 99%